Antibacterial effect of corarian seed (Coriandrum sativum L.) extract on Streptococcus mutans - Kodariah, Liah; Ghasani, Firzanah; Murtafi'ah, Ni'matul (Lighthouse Publishing, 2022)
Dental plaque plays an important role in causing dental caries. In plaque formation, gram-positive coccus bacteria are found, one of which is Streptococcus mutans which can secrete toxins so that tooth cells are damaged. Dental plaque or dental caries can be controlled in number by controlling plaque with antimicrobial agents such as mouthwash. However, the continuous use of antimicrobials can cause side effects for users, including hypersensitivity reactions and resistance, so it is necessary to use natural ingredients as antibacterial alternatives. Therefore, this study used coriander seeds as an alternative to inhibit the growth of Streptococcus mutans bacteria. The purpose of this study was to determine the effectiveness of coriander seed extract (Coriandrum sativum L.) with varying concentrations on the growth of Streptococcus mutans bacteria. This study used the diffusion method as a bacterial test method for coriander seed extract. The concentrations tested in this study were 3%, 6% and 9%. Based on the results of the study showed that there was an inhibition zone in the test of coriander seed extract against Streptococcus mutans. At a concentration of 3% the average inhibition zone was 3.7 mm, the concentration of 6% was 4.7 mm and concentration of 9% by 6.06 mm. The results of this study concluded that coriander seed extract (Coriandrum sativum L.) was effective in inhibiting the growth of Streptococcus mutans bacteria.